KONSTRUKSI IDENTITAS PADA INDIVIDU YANG MEMILIKI LEBIH DARI SATU INSTAGRAM - Kristanti, Veronica Dinda Sekar; Harimurti , Albertus (Atma Jaya Catholic University of Indonesia, 2023)
This research aims to understand how identity is constructed in individuals who have more than one Instagram account. The study employs a qualitative approach, and data collection is carried out by involving 10 informants through online semi-structured interviews. The collected data is analyzed using narrative analysis methods. Based on the analysis results, five themes are identified that demonstrate the identity construction of individuals on their Instagram accounts: 1) Feelings of insecurity; 2) Anticipatory anxiety; 3) Self-image as public identity; 4) Limitations of private identity; and 5) Existential anxiety in community space. Informants position themselves as individuals who feel insecure and strive to overcome anticipatory anxiety. These two themes are further related to the informants' public identity that portrays their self-image and their attempts to limit their private identity. The formation of public and private identities by informants also serves as an effort to address informants' existential anxiety within the community space.